Use of the Cutaneous Lupus Disease Area and Severity Index as an outcome measure in clinical trials: a descriptive study. (1st October 2020) - Mack, E.; Exton, L.S.; Mohd Mustapa, M.F.; McCourt, C.; O'Kane, D.
Summary: This study summarizes the use, since its inception, of the Cutaneous Lupus Disease Area and Severity Index (CLASI) as an outcome measure in clinical studies. We systematically searched the MEDLINE, PubMed, EMBASE and Cochrane databases for papers including the term 'cutaneous lupus disease area and severity index' and its abbreviations up to August 2017, identifying 205 abstracts. Following shortlisting, two independent physicians critically reviewed 71 papers for data extraction. We found that a limited number of high‐quality studies used the CLASI scoring as an outcome measure. We concluded that further validation is necessary to identify the effectiveness of the CLASI in the assessment of cutaneous lupus erythematosus subtypes. The use of standardized core patient‐ and physician‐reported outcome measures may reduce heterogeneity and allow comparisons between patients enrolled in clinical trials. This would improve the relevance within clinical practice, where the use of CLASI is currently limited.